2015
DOI: 10.1118/1.4905041
|View full text |Cite
|
Sign up to set email alerts
|

A deterministic solution of the first order linear Boltzmann transport equation in the presence of external magnetic fields

Abstract: The feasibility of including magnetic field effects in a deterministic solution to the first order linear Boltzmann transport equation is shown. The results show a high degree of accuracy when compared against Monte Carlo calculations in all magnetic field strengths and orientations tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The stationary CSD linear Boltzmann transport equation in magnetic fields is derived in the following form (St-Aubin et al 2015,…”
Section: Continuous Slowing Down (Csd) Linear Boltzmann Transport Equmentioning
confidence: 99%
“…The stationary CSD linear Boltzmann transport equation in magnetic fields is derived in the following form (St-Aubin et al 2015,…”
Section: Continuous Slowing Down (Csd) Linear Boltzmann Transport Equmentioning
confidence: 99%
“…Discrete ordinates (DO) represents a classical angular technique where the LBTE is solved along discrete transport directions which are chosen from numerical quadrature sets (Lewis and Miller 1993). It has been successfully applied to radiotherapy (Vassiliev et al 2010, however in the presence of magnetic fields, the solution stability was found to be conditional on many parameters including magnetic field strength, and the material interaction cross section (St-Aubin et al 2015, Zelyak et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Although machine specifications, magnetic field orientations and strengths differ in these studies, all have found that the dose is distorted by the magnetic field, especially at air-tissue-interfaces in lung and skin. However, dedicated dose calculation algorithms, which are based either on Monte Carlo methods or on solving of the linear Boltzmann transport equation, are able to account for the presence of magnetic fields [107][108][109]. Several studies have shown that using such dose calculation algorithms to account for the ERE during treatment plan optimization allows for the design of clinically acceptable lung SBRT treatments [104][105][106].…”
Section: Delineation Dose Calculation and Treatment Planningmentioning
confidence: 99%